Study Some Differential Subordination and Superordination Results Involving of Certain Class - Mustafa I. Hameed; Shaheed Jameel Al-Dulaimi (Genius Journals, 2022)
Meromorphic Functions, Differential Subordination, Superordination, Sandwich Theory, Starlike Functions, Convex Functions, Hadamard Product
Keywords: COVID-19 Pandemic; Organic chemistry; Students; Iraqi universities